Poverty and large family size are pivotal risk factors for child marriage in Ethiopia: evidence from a matched case-control study - Gelchu Adola, Shiferaw; Wirtu, Dessalegn; Dheresa, Merga (Frontiers in Sociology, 2025)
BackgroundChild marriage is a marriage carried out before the age of 18 years old which is influenced by numerous cultural, social, and economic factors, and it is a source of gender inequality, violence against women, and various maternal and child health problems. Therefore, this study aimed to identify risk factors of child marriage in the West Guji zone of southern Oromia, Ethiopia.MethodsA community-based 1:2 matched case-control study design was conducted from April 1 to May 5, 2024. The purposive sampling technique was used to select 120 pairs (120 cases and 240 controls). Age was selected as a matching variable, and for each case, two best-matched controls were selected. The questionnaires were administered through a face-to-face interview. Both binary and multivariable conditional logistic regressions were conducted to determine independent determinants of child marriage. In the multivariable model, statistical significance was established at p < 0.05. The strength of the association was reported by the matched adjusted odds ratio (mAOR) with 95% CI.ResultsWomen from medium family size (4–6 members) were nearly four times more likely to be married early as compared to women from small family size (≤ 3 family members) (mAOR: 3.87, 95% CI = 1.56–9.55). The odds of early marriage were five-fold greater among women from larger families (mAOR: 5.09, 95% CI = 1.53–16.90). The odds of being married younger than 18 years were nearly three times greater among women who were not aware of the legal age of marriage (mAOR: 2.92, 95% CI = 1.27–6.68). Women whose marriage decision was made by others were two times more likely to be married early (mAOR: 2.47, 95 CI = 1.30–4.71). The risk of marriage under 18 years of age was seven-fold greater among women from the poor parental wealth category than among those from the rich category (mAOR: 7.65, 95%CI = 2.48–13.07).ConclusionPoor family wealth statuses, larger parental family size, not knowing the legal marital age, and marriage decision by others, were risk factors for child marriage. As a result, to stop child marriage in rural Ethiopia, policies and strategies that take into account these factors should be developed and put into practice.